A siRNA-induced peptide co-assembly system as a peptide-based siRNA nanocarrier for cancer therapy. Issue 4 (14th June 2018) - Li, Wenjun; Wang, Dongyuan; Shi, Xiaodong; Li, Jingxu; Ma, Yue; Wang, Yanding; Li, Tingting; Zhang, Jianing; Zhao, Rongtong; Yu, Zhiqiang; Yin, Feng; Li, Zigang
Abstract : Herein, we report a unique siRNA-induced peptide co-assembly nanocarrier, which could efficiently co-assemble upon the addition of siRNA, forming nanospheres with high biocompatibility and transfection efficiency both in vitro and in vivo . Abstract : Herein, we report a unique siRNA-induced peptide co-assembly nanocarrier, which could efficiently co-assemble upon the addition of siRNA, forming nanospheres with high biocompatibility and transfection efficiency both in vitro and in vivo . In a tumor xenograft nude mouse model, these siRNA–peptide nanospheres inhibited tumor volume growth by >60%.